Bacteriological Profile and Antibiotic Subsceptiblity Patterns of Asymptomatic UTI among Female Students of R.R.M Campus Janakpurdham, Madhesh Pradesh, Nepal (Tribhuvan University Journal of Microbiology, 2025)
Objective: The primary goal of this study was to identify common pathogenic microorganisms and their patterns of antibiotic susceptibility from asymptomatic UTI cases.Methods: A Total of 151 mid-stream urine samples were collected from female students for bacteriological identification and antimicrobial susceptibility testing. Conventional biochemical tests identified the isolates, and their antibiotic susceptibility was determined according to the Clinical and Laboratory Standards Institute (CLSI) guidelines.Results: Of the 151 samples analyzed, 30.46% exhibited significant bacterial growth, with Staphylococcus aureus being the most prevalent (30.43%), followed by Escherichia coli (17.39%) and Klebsiella pneumoniae (10.86%). Gram-negative bacterial isolates showed a higher level of resistance to amoxicillin (33%-100%), amoxicillin (60%-100%), amoxicillin-clavunic acid (20%-100%), ceftriaxone (60%-100%), cotrimoxazole (40%-100%), nitrofurantoin (40%-100%), and ciprofloxacin (40%-100%). Piperacillin and Tazobactam, levofloxacin, imipenem, and amikacin were less resistant. Gram-positive bacterial uropathogens showed a high level of resistance to amoxicillin (65%-100%), ciprofloxacin (50%-100%), levofloxacin (50%-100%), and clindamycin (64%-100%). Imipenem, gentamicin, piperacillin, and tazobactam have shown reduced resistance.Conclusion: Uropathogens were found to be highly prevalent, and bacterial isolates were shown to be highly resistant to routinely recommended medications. In order to prevent an asymptomatic infection from developing into a symptomatic UTI, routine UTI screening, regular health education on the risk of asymptomatic infectious diseases for females in the reproductive age group, and antibiotic susceptibility testing should be implemented.